The impact of production methods and row orientation on carrot quality in the case of various cultivars - Kiss, Péter; Takácsné Hájos, Mária (Acta Agraria Debreceniensis, 2014)
Carrot is a wellknown and favoured, really important vegetable. Carrot’s cultivation is important, although its growing field has been reduced in last few years. The suitable cultivar and landstructure are essential to produce good quality carrot. The ridge cultivation is widely spread on plasted soils. At this type of cultivation relationship between line orientations and carrot quality is less studied. That is the reason we tried to examine in our experiment the relationship between ridge highness and line orientation (N-S and E-W) and carrot’s morphological features at different genotipes. The experimental was settled in the Experimental Garden of the University of Debrecen on limy chernozem soil by plain, raised bed and ridge cultivation in 2013. In the experiment we examined four longgrowing cultivars (Danvers 126, Fertődi vörös, Rekord, Chantenay). The sowing was at 24th April. The harvest was at 15th October, 2013. In the multi factorial (type of cultivation, line orientation, cultivar) experimental we explained the effect of treatments on carrot root shoulder diameter and root weight.In our experiment we stated that line orientation had no significant effect on shoulder diameter at different cultivations. The only exception is Fertődi vörös which has reached the biggest shoulder diameter (5 cm